Water quality : - Boyd, Claude E. (Kluwer Academic Publishers, 2015)
This book presents the basic aspects of water quality, emphasizing physical, chemical, and biological factors. The study of water quality draws information from a variety of disciplines including chemistry, biology, mathematics, physics, engineering, and resource management.